Pernikahan Penyandang Disabilitas Perspektif Hukum Perkawinan Indonesia Dan Fiqh - Hidayatul Firdaus, Dwi; Ch, Mufidah; Suwandi (At-Tahdzib: Jurnal Studi Islam dan Muamalah, 2022)
Background. Marriage is a lawful and main way to realize and maintain human honor, because by marrying people can avoid behaviors that are forbidden by Allah SWT. As normal human beings in their human instincts, persons with disabilities are also gifted with sexual desire and the desire to continue their offspring in a grand procession called marriage. However, with the various shortcomings that exist in them, they are worried that they will have difficulty in carrying out the life of the ark of their household life.Aim. For this reason, it is necessary to know how marriages carried out by persons with disabilities are in the eyes of legislation and Islamic law, and this requires legal certainty.Methods. This literatur study purpose to determine and analyze: Marriage Law for Persons with Mental Disabilities according to Law No. 1 of 1974 and Law no. 8 of 2016. This research method uses library research methods, namely research that collects data and information with the help of various materials contained in the literature.Results. The results of this study are that legally, marriages for people with mental disabilities are still legal in terms of harmony and there is no damage or there must be an annulment in terms of the terms of marriage. Because for people with mental disabilities, whether prospective brides or grooms, there are no criteria, they must be healthy and respond to the needs of contemporary life such as human rights, gender, environment, democracy and others.